Representasi Maskulinitas Perempuan dalam Iklan Sasa Melezatkan berjudul Perempuan Serba Bisa - Ramadhani, Fadila Elma; Budiyono, Alief (Universitas Islam Balitar, 2024)
Advertising has a big influence in shaping people's perceptions and views on various issues, including gender and the role of women. This research analyzes the representation of women's masculinity in the Sasa Melezakan advertisement entitled